The underappreciated diversity of furanocoumarins in grapefruits revealed by MassQL filtered molecular networking - Shilin Gong; Guoyu Bai; Yujuan Ban; Meixian Liu; Ying Liu; Yuyao Wu; Na Li; Jian-Lin Wu (Food Chemistry: X)
Grapefruit is one of the most popular Citrus fruits, which is beneficial for health. Coumarins are the main secondary metabolites in grapefruits. The structural and functional diversity makes the comprehensive determination of coumarins in complex system necessary and challenging. Here a rapidly profiling strategy integrating LC–MS and mass data filter tool MassQL with molecular networking for coumarin focusing was established. A total of 134 coumarins were tentatively annotated, including 17 potential new compounds. Analysis of structural characters revealed the large number of furanocoumarins and the biosynthesis preference of O-geranylation in grapefruits. Further analysis showed coumarins might differentiate grapefruit varieties. Moreover, typical biofunctions analysis indicated furanocoumarins contributed a lot to the total activities of grapefruits, when grapefruit-Thompson with a potential to generate better biological effects than grapefruit-Marsh. This study provided a comprehensive profiling strategy for coumarins, which could support the varieties selection when developing functional products of grapefruits.